Mediation as a policy instrument for resolving environmental disputes: With special reference to Germany - Helmut Weidner (Wissenschaftszentrum Berlin für Sozialforschung (WZB); Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1993)
Environmental conflicts are on the increase in all democratic industrial societies. In some areas, especially those involving big technology development projects, there is growing resistance to government intervention using conventional policy instruments. Therefore, political administrations and business have begun to accept the idea of experimenting with so-called alternative forms of conflict resolution, in particular, those based upon negotiation. In the United States, Japan, and Canada one such procedure, mediation, has come into wider use and proven successful in practice. This article describes several mediation procedures, mostly in the United States, but also including two examples of its application for resolving conflicts in the Federal Republic of Germany-one concerning a landfill site at Münchehagen and one concerning a waste management concept for the county [Kreis] of Neuss in the German Federal State of North Rhine-Westphalia. Finally, the question is raised in general as to whether and how mediation procedures could fUnction as policy instruments in a modern state, and whether they are appropriate for dealing with major, but at the same time locally restricted cases of conflict. Regarding the Federal Republic of Germany in particular, more practical experience with mediation must be gained before we are able to draw general conclusions about its possible areas of application in this country and the conditions underlying its success. – – In allen demokratischen Industriegesellschaften nehmen die Umweltkonflikte zu. Einige Bereiche (besonders groBtechnische Entwicklungsvorhaben betreffend) erweisen sich zunehmend resistenter gegen staatliche Steuerungsversuche mit konventionellen Politikinstrumenten. Das hat im politisch-administrativen System und in der Wirtschaft die Bereitschaft wachsen lassen, mit neuartigen, sog. alternativen Streitregelungsverfahren zu experimentieren. Sie beruhen in aller Regel auf Verhandlungslosungen. Eines davon, das Mediationsverfahren, hat sich in der Praxis - insbesondere in den USA, Japan und Kanada - als relativ erfolgreich erwiesen. Es wird in diesem Beitrag vor dem Hintergrund besonders der Erfahrungen in den USA beschrieben, weiterhin werden zwei Anwendungsfalle in der Bundesrepublik Deutschland (Mülldeponie Münchehagen, Abfallwirtschaftskonzept des Kreises Neuss) dargestellt. SchlieBlich wird der Frage nachgegangen, ob und in welcher Weise Mediationsverfahren als Politikinstrumente angesehen werden konnen. Die Studie kommt zu dem Ergebnis, daB Mediationsverfahren Politikinstrumente eines modernisierten Staates sind und besonders fur groBe, jedoch lokal/regional überschaubare Konflikte geeignet sind. In der Bundesrepublik Deutschland sind allerdings noch mehr praktische Erfahrungen notwendig, um über Erfolgsvoraussetzungen und Anwendungsgebiete begrundete allgemeinere Aussagen machen zu konnen.
Keywords: 320